Failures of homogeneous and isotropic cosmologies in extended quasidilaton massive gravity - Anselmi, Stefano (2017)
We analyze the extended quasidilaton massive gravity model around a Friedmann-Lemaître-Robertson- Walker cosmological background. We present a careful stability analysis of asymptotic fixed points. We find that the traditional fixed point cannot be approached dynamically, except from a perfectly fine-tuned initial condition involving both the quasidilaton and the Hubble parameter. A less-well examined fixed- point solution, where the time derivative of the zeroth Stückelberg field vanishes φ_ 0 1⁄4 0, encounters no such difficulty, and the fixed point is an attractor in some finite region of initial conditions. We examine the question of the presence of a Boulware-Deser ghost in the theory. We show that the additional constraint that generically allows for the elimination of the Boulware-Deser mode is only present under special initial conditions. We find that the only possibility corresponds to the traditional fixed point and the initial conditions are the same fine-tuned conditions that allow the fixed point to be approached dynamically.